Vitality and burnout of employees in Christian humanitarian organisations : the role of need satisfaction at work and religious beliefs : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Williams, Tamara Joanne (Massey University, 2012)
Humanitarian workers are at relatively high risk of developing a range of negative outcomes in response to stress. For individual employees, the organisations they represent, and the people they serve, it is important to examine workplace wellbeing. This research analysed vitality and burnout as constructs of wellbeing in employees of international, Christian humanitarian organisations based in Chennai, India. This wellbeing dichotomy was explored through two main factors: basic psychological need satisfaction at work, and religious beliefs. These two factors were examined through a Self-Determination Theory framework. Data was collected via a questionnaire comprised of psychometrically established measures and six open-ended questions for supplementary qualitative data. There were 99 respondents. The results demonstrated the importance of supporting autonomy, competence and relatedness (basic psychological needs) in employees of humanitarian organisations. Workplace support leading to basic need satisfaction was associated with increased vitality and decreased levels of burnout. Autonomous motivations for religious beliefs were positively associated with vitality, and non-autonomous motivations for religious beliefs were linked with decreased burnout. The use of religious coping was not as clearly linked with these wellbeing constructs except that the presence of negative religious coping was positively related to burnout. The findings are pertinent for humanitarian organisations, particularly those with a Christian foundation, to understand and facilitate factors that increase vitality and decrease burnout in the workplace.
Keywords: Religious institutions; Church charities; Humanitarian workers; Non-governmental organisations; Employees; Job stress; Job satisfaction; Subjective vitality; Burnout; Basic need satisfaction at work; Internalisation of religious beliefs; Religious coping